2016
DOI: 10.1111/hel.12360
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Helicobacter pylori infection in newly arrived refugees attending the Migrant Health Service, South Australia

Abstract: H. pylori infection is common among newly arrived refugees. The long latency of infection to development of complications and the availability of testing and relatively effective eradication regimens all add weight to a decision to screen in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 23 publications
0
9
2
Order By: Relevance
“…During another study, 52% of patients were H. pylori positive which was compatible with the current investigation ( 3 ). In an Australian survey, prevalence rate was 21.5% which was less than present results ( 15 ). The cause of these varieties may be due to different socioeconomic levels between communities.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…During another study, 52% of patients were H. pylori positive which was compatible with the current investigation ( 3 ). In an Australian survey, prevalence rate was 21.5% which was less than present results ( 15 ). The cause of these varieties may be due to different socioeconomic levels between communities.…”
Section: Discussioncontrasting
confidence: 86%
“…The cause of these varieties may be due to different socioeconomic levels between communities. In the present study, there was no sex predominance in prevalence of H. pylori infection, whilst Yucel et al ( 16 ) indicated a higher prevalence rate among females but Abdul Rahim et al reported male predominance ( 15 ). Our results indicated no association between sex and positivity of serum and salivary IgG against H. pylori.…”
Section: Discussioncontrasting
confidence: 58%
“…Conversely, the prevalence of H. pylori infection remains high in newly arrived refugees attending the migrant health service in South Australia, where 922 adults and children were screened in a cross‐sectional study using the monoclonal HpSA. H. pylori infection was detected in 198 (21.5%) patients . A Chinese school‐based cross‐sectional study in Shanghai was conducted in 1,988 students using UBT.…”
Section: Epidemiologymentioning
confidence: 99%
“…H. pylori infection was detected in 198 (21.5%) patients. 6 A Chinese school-based crosssectional study in Shanghai was conducted in 1,988 students using UBT. Overall positive UBT was found in 36.3% (721/1,988).…”
Section: Epidemiologymentioning
confidence: 99%
“…Upper abdominal discomfort secondary to a bacterial stomach infection with Helicobacter pylori. H pylori infection is common among newly arrived refugees (Abdul Rahim et al, 2017).…”
Section: Case Studymentioning
confidence: 99%